God 2.0? - Lysaught, M. Therese (Hastings Center Report)
Robert L. Klitzman's Doctor, Will You Pray for Me? Medicine, Chaplains, and Healing the Whole Person (Oxford University Press, 2024) offers a fervent apology for the increasingly crucial role of chaplains in contemporary health care. It weaves together anthropological data from interviews with a chaplain cohort, personal narrative, patient stories, chaplain testimony, and the social scientific study of religion. It also surfaces pointed questions about the assumptions that shape contemporary chaplaincy and the directions in which it is moving. These questions include the following: How might we clarify and strengthen the ambiguous and tensive relationship between chaplaincy and bioethics? How do we assess the normativity of the perduring Kantian/Jamesian account of religion and spirituality, which is highly individualized and emotivist? And in light of this, is chaplaincy simply becoming the institutionalized form of religion for twenty‐first‐century neoliberalized health care?.